Slavery, Royalty, and Racism: Representations of Africa in Brazilian Carnaval - Araujo, Ana Lucia (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2010)
This paper examines the representations of Africa in Rio de Janeiro’s carnaval. During the second half of the twentieth century, Afro-Brazilian self-assertion movements took inspiration from the African American movement for civil rights. At the same time, public cultural assertion largely relied on recreated connections with Africa, often perceived as an idealized continent. This Africanization, first developed at the religious level, later also became visible in other cultural manifestations such as music, dance, fashion, and carnaval. The analysis of the example of the escolas de samba’s parades held during Rio de Janeiro carnaval since the 1950s demonstrates how the promotion of bonds with “Africa” is part of a reconstruction process in which the South Atlantic becomes a common zone of claims for recognition of multiple identities, in which the legacy of slavery and the slave trade is reconstructed and renewed.